PERSEPSI PENGUNJUNG TERHADAP PENGELOLAAN KAWASAN WISATA BUKIT KASIH KANONANG - Yusviana Botha; Fabiola B. Saroinsong; Hard N. Pollo (COCOS, 2017)
ABSTRACTImproving management efforts of a tourist area as in Bukit Kasih Kanonang Tourism Area could be based on the perception of visitors. Interview Method was used to collect data from 100 respondents for a two-month research period that was done on every Saturday and Sunday. Visitor perception assessment was using Likert Scale. The result showed that the visitor perception level is in between of 255 - 904 with the average value was on 575.5. Based on the value gained, it can be concluded that visitor perception level was not good to good enough. It means that the improving management efforts are necessary.Keywords : Management Improvement, Likert Scale, Visitor Perception, Bukit Kasih Kanonang